Anaesthesia suitable for prolonged bronchoscopic examination - Attwood, E. C. (1970)
A technique of combined general and topical anaesthesia is described involving spontaneous ventilation. Patients aged 46 to 76 were examined in this way for periods varying between 5 and 25 minutes. Carbon dioxide elimination was satisfactory in all but 2 of 18 patients, and these 2 are discussed in detail. Capillary oxygen tension was maintained at a level of over 75 mm. Hg throughout all 11 examinations where oxygen was introduced at the proximal end of the bronchoscope, but dangerous hypoxaemia occurred in 2 patients in whom oxygen was not administered in this way.